Kidney Function and Extreme Endurance Races: Risks, Mechanisms, and Preventing Strategies - Kulbacka, Julia; Dziedzic, Karol; Arczewski, Filip; Wójcikiewicz, Michalina; Chuncia-Ileczko, Marta; Kacperczyk, Julia; Czyż, Witold; Zys, Damian; Pasek, Piotr; Ryniecka, Julia (Quality in Sport, 2025)
Background: The increasing popularity of ultra-endurance sports emphasizes the need for a deeper understanding of their health implications, particularly the impact on kidney function. Given the kidneys’ crucial role in waste filtration, fluid and electrolyte balance, and their close connection to the physiological demands of intense physical activity, it requires detailed investigation from this perspective. Purpose: The objective of this study is to present the current state of knowledge on the topic of kidney function in the context of ultra-endurance sports. It examines the risk factors, underlying mechanisms, and potential strategies for preventing renal injuries associated with these specific types of physical activities. Findings: Ultra-endurance sports present significant risks to kidney health, including acute kidney injury (AKI) estimated to affect approximately 40% of participants, rhabdomyolysis and dehydration, which are often compounded by additional factors such as gastrointestinal distress and the use of non-steroidal anti-inflammatory drugs (NSAIDs). There is a need for improved diagnostic criteria to detect acute renal injury in this population, with novel biomarkers such as neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), and cystatin C showing promise. A multifaceted preventive approach including strategies such as mandatory pre-event screening, the use of personal monitoring devices, proper hydration and nutrition, adequate race preparation, and the avoidance of NSAIDs is crucial to mitigate these risks and maintain renal health in ultra-endurance athletes.